Affordability and Availability of Pasteurized Donor Human Milk. Issue 6 (November 2017) - Spatz, Diane L.
Abstract : The American Academy of Pediatrics (AAP) released a new position statement on Pasteurized Donor Human Milk (PDHM) earlier this year, emphasizing the importance of PDHM for hospitalized infants. The position statement highlights the need for PDHM for infants less than 1500 grams but acknowledges that there may be a role for PDHM to be used for other infants such as those with abdominal wall defects. Our breastfeeding expert, Dr. Diane Spatz, discusses this issue in detail.